Ceriomicrodon petiolatus Hull, 1937 (Diptera, Syrphidae, Microdontinae): Redescription and new records - Miranda, Gil Felipe Gonçalves (Zootaxa, 2014)
The monotypic genus Ceriomicrodon Hull, 1937 was known in the current literature by a few specimens, all from Brazil but with records only for Mato Grosso and Roraima states. The only species of the genus is here redescribed including the description of the female and its terminalia, in addition to a preliminary description of the egg. Images of male and female genitalia and egg are provided. New Brazilian records for Amazonas, Maranhão and Rondônia and a brief diagnosis to distinguish that genus from other similar Microdontinae genera are presented.